TEACHER'S TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) IN NEW NORMAL ERA - Imadul Bilad; Achmad Anang Darmawan; Lina Aris Ficayuma (STKIP AL HIKMAH SURABAYA, 2023)
Recognizing that each teacher has unique strengths, preferences, and learning styles, they tailored their instructional approach accordingly. By aligning their teaching methods with their own characteristics, they were able to optimize TPACK development and create meaningful and engaging learning experiences for their students.